THE EFFECTIVENESS OF MIND MAPPING IN CONSTRUCTING ARGUMENTS IN WRITING AN ARGUMENTATIVE TEXT - Eva Rosita; Sisilia Setiawati Halimi (IJEE (Indonesian Journal of English Education), 2023)
ABSTRACTThe ability to compose and develop ideas in argumentative writing has become a challenge for grade XI students in a private high school in Indonesia, and mind mapping is believed in the literature to be a potential strategy to overcome the challenge. This mixed-method experimental study, therefore, was designed to examine the effectiveness of mind mapping as a prewriting strategy. The study's results, which compared the pre-test and post-test scores analyzed using the Nonparametric-Wilcoxon Signed Rank Test, showed a significant value in the experimental group with Asymp Sig. (two-tailed) 0.003<0.05. The participants also expressed their perceptions of the mind-mapping features through a questionnaire and interview. Data analysis conducted using In Vivo coding in this research showed that the mind-mapping elements with the most significant influence on content exploration, text structure, convenience and interest in writing, time efficiency, and thinking skills were keywords, colors, and branches. Nevertheless, three participants said they did not make any progress for several reasons. The significant finding and the vast majority of positive opinions indicated that mind mapping was an effective strategy for developing ideas in argumentative writing. In further research, it would be interesting to explore how this strategy could be applied to a larger learning community by combining it with other strategies to improve learning outcomes.ABSTRAKTantangan pada penulisan teks argumentatif yang dihadapi pelajar kelas XI di sebuah Sekolah Menengah Atas (SMA) swasta di Indonesia terletak pada kemampuan menyusun dan mengembangkan gagasan. Maka, kendala tersebut diatasi melalui studi eksperimental menggunakan metode campuran dengan menerapkan prewriting berbentuk mind mapping. Hasil penelitian berupa perbandingan nilai pre-test dan post-test yang dianalisis menggunakan Nonparametric-Wilcoxon Signed Rank Test menunjukkan nilai yang signifikan pada experimental group dengan Asymp.Sig.(2-tailed) 0.003<0.05. Partisipan kemudian mengungkapkan persepsinya terhadap penggunaan mind mapping melalui kuesioner dan wawancara yang dianalisis menggunakan teknik In Vivo coding. Dari hasil analisis, diketahui bahwa kata kunci, warna, dan cabang merupakan komponen mind mapping yang paling berdampak pada eksplorasi konten, struktur teks, kemudahan dan minat menulis, efisiensi waktu, serta keterampilan berpikir. Meskipun demikian, terdapat 3 orang partisipan yang mengungkapkan bahwa mereka tidak merasakan perkembangan karena penyebab tertentu. Signifikansi hasil penelitian dan persepsi yang mayoritas positif menyiratkan bahwa mind mapping merupakan strategi yang cocok untuk mengembangkan gagasan pada penulisan teks argumentatif. Maka, pada penelitian selanjutnya, menarik untuk melihat fungsi mind mapping pada komunitas belajar yang lebih besar dan menggabungkannya dengan strategi lain untuk mengoptimalkan hasil belajar.How to Cite: Rosita, E., Halimi, S. S. (2023). The Effectiveness of Mind Mapping in Constructing Arguments in Writing an Argumentative Text. IJEE (Indonesian Journal of English Education), 10(1), 126-143. doi:10.15408/ijee.v10i1.31848